UPAYA MENINGKATKAN KECERDASAN EMOSIONAL MELALUI METODE PROYEK ANAK USIA 5-6 TAHUN DI TK BHAKTI IBU KOTA PEKANBARU - Miyarti, Isra; Nurdin, Zulkifli; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is high intellectual intelligence children with low emotional intelligence phenomenon. This research conducted for knowing the effect of project method learning for increasing emotional intelligence and how far it will increased. The sample for this research are 20 children around 5-6 years old in Bhakti Ibu Kindergarten Pekanbaru City, consist of 12 boys and 8 girls. This research is Classroom Action Research. It using observation page as information collecting method. This research divided in 2 cycles with 3 meetings in each cycle. From this research, collected that percentage of emotional intelligence increased from before action to first cycle is 30,30%. Percentage of emotional intelligence increased from first cycle to second cycle is 42,33%. Furthermore, emotional intelligence increased from before action to second action is 85,46%. From this research concluded that project method activities could increase emotional intelligence for 5-6 years old children in Bhakti Ibu Kindergarten Pekanbaru City.Key words: emotional intelligence, project method